The Transylvania Television Real meanin' of Halloween special show - Heagle, Michael J.; Gallagher, Matthew; Transylvania Televison Workshop (Firm); Leomark Studios (Firm) ([United States] : Transylvania Television Production, 2012)
When the Vampire Le Shoc leaves the castle for Halloween to avoid a curse, Von Bucket sets up a proper party. Furry Ackermonster is schooled about the holiday and seeks the Real Meaning of the holiday in the bowels of the castle. Le Shoc meets his match while trapped at the airport, and Von Bucket encounters a surprising party guest. Dwayne Frankenstein awaits the annual arrival of the Pumpkin Prince and is not disappointed.--
Originally released as a television program in 2010
Series created by Michael Heagle, Gordon Smuder.
Editors, Michael Heagle, Troy La Faye ; music, John Mapes, DJ Sothoth, Interantional Espionage, David Last.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 25, 2018)
Keywords: Halloween -- Drama; Puppet television programs; Animated television programs; Television comedies; Webisodes; Internet videos; Streaming video